2020
DOI: 10.1039/c9sc05909a
|View full text |Cite
|
Sign up to set email alerts
|

Solar water splitting over Rh0.5Cr1.5O3-loaded AgTaO3 of a valence-band-controlled metal oxide photocatalyst

Abstract: One-step photoexcitation type solar water splitting with a valence-band-controlled metal oxide photocatalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 28 publications
1
21
1
Order By: Relevance
“…Water photolysis is known to be the most optimal procedure for acquiring solar hydrogen. Since the discovery of the water splitting system comprising a titanium(IV) dioxide (TiO 2 ) photoanode by Honda and Fujishima, [1] numerous studies on water splitting by both photoelectrochemical and photocatalytic methods have been conducted [2–12] . As a long‐standing issue, the development of active photocatalyst materials, which are able to efficiently utilize the solar spectrum for high output of molecular hydrogen, is required.…”
Section: Introductionmentioning
confidence: 99%
“…Water photolysis is known to be the most optimal procedure for acquiring solar hydrogen. Since the discovery of the water splitting system comprising a titanium(IV) dioxide (TiO 2 ) photoanode by Honda and Fujishima, [1] numerous studies on water splitting by both photoelectrochemical and photocatalytic methods have been conducted [2–12] . As a long‐standing issue, the development of active photocatalyst materials, which are able to efficiently utilize the solar spectrum for high output of molecular hydrogen, is required.…”
Section: Introductionmentioning
confidence: 99%
“…In the same way, also Zn 1.44 GeN 2.08 O 0.38 decorated with RuO 2 was reported for overall water splitting, [40] and photodeposition of Rh 2‐y Cr y O 3 also resulted in water splitting activity [38] . Recently, AgTaO 3 was decorated with a similar co‐catalyst with defined stoichiometry, Rh 0.5 Cr 1.5 O 3 , resulting in overall water splitting with an apparent quantum yield of 40 % at 340 nm an a solar‐to‐hydrogen efficiency of 0.13 % [41] …”
Section: Single Absorber Materialsmentioning
confidence: 99%
“…[38] Recently, AgTaO 3 was decorated with a similar co-catalyst with defined stoichiometry, Rh 0.5 Cr 1.5 O 3 , resulting in overall water splitting with an apparent quantum yield of 40 % at 340 nm an a solar-to-hydrogen efficiency of 0.13 %. [41] Searching for visible light absorbing materials, TiO 2 played an important role in materials research. A very prominent strategy in the early 2000s was non-metal doping of stable and well-known oxides, [42] including TiO 2 , with e. g. nitrogen and/or sulfur anions.…”
Section: Single Absorber Materialsmentioning
confidence: 99%
“…16 We have also reported that Rh 0.5 Cr 1.5 O 3 -loaded AgTaO 3 (BG 3.4 eV) shows high AQY (38% at 340 nm) and STH (0.13%) for water splitting. 17 The valence band maximum (VBM) of the Al-doped SrTiO 3 is formed by O2p orbitals, while that of the AgTaO 3 is formed by Ag4d orbitals. 18 A photocatalyst whose valence band (VB) is formed by orbitals of elements except oxygen like AgTaO 3 is called a valence-band (VB)-controlled photocatalyst.…”
mentioning
confidence: 99%
“…18 A photocatalyst whose valence band (VB) is formed by orbitals of elements except oxygen like AgTaO 3 is called a valence-band (VB)-controlled photocatalyst. 3,17,19 The VBcontrolled photocatalyst is very important from the viewpoint of extension of responsive wavelength. Although the STH of the Rh 0.5 Cr 1.5 O 3 -loaded AgTaO 3 is the highest among the VBcontrolled photocatalysts, the BG of the AgTaO 3 is wider than that of the Al-doped SrTiO 3 .…”
mentioning
confidence: 99%